A novel leucine‐rich repeat protein, CaLRR51, acts as a positive regulator in the response of pepper to Ralstonia solanacearum infection. (20th September 2016) - Cheng, Wei; Xiao, Zhuoli; Cai, Hanyang; Wang, Chuanqing; Hu, Yang; Xiao, Yueping; Zheng, Yuxing; Shen, Lei; Yang, Sheng; Liu, Zhiqin; Mou, Shaoliang; Qiu, Ailian; et al.
Summary: The leucine‐rich repeat (LRR) proteins play important roles in the recognition of corresponding ligands and signal transduction networks in plant defence responses. Herein, a novel LRR protein from Capsicum annuum, CaLRR51, was identified and characterized. It was localized to the plasma membrane and transcriptionally up‐regulated by Ralstonia solanacearum infection (RSI), as well as the exogenous application of salicylic acid (SA), jasmonic acid (JA) and ethephon (ETH). Virus‐induced gene silencing of CaLRR51 significantly increased the susceptibility of pepper to RSI. By contrast, transient overexpression of CaLRR51 in pepper plants activated hypersensitive response (HR)‐like cell death, and up‐regulated the defence‐related marker genes, including PO2, HIR1, PR1, DEF1 and ACO1 . Moreover, ectopic overexpression of CaLRR51 in transgenic tobacco plants significantly enhanced the resistance to RSI. Transcriptional expression of the corresponding defence‐related marker genes in transgenic tobacco plants was also found to be enhanced by the overexpression of CaLRR51, which was potentiated by RSI. These loss‐ and gain‐of‐function assays suggest that CaLRR51 acts as a positive regulator in the response of pepper to RSI. In addition, the putative signal peptide and transmembrane region were found to be required for plasma membrane targeting of CaLRR51, which is indispensable for the role of CaLRR51 in plant immunity.